Comparative genomics of canine parvovirus in South America: Diversification patterns in local populations - Grecco, Sofía (2024)
Canine parvovirus (CPV) is a significant pathogen in domestic dogs worldwide, causing a severe and often fatal disease. CPV comprises three antigenic variants (2a, 2b, and 2c) distributed unevenly among several phylogenetic groups. The present study compared genetic variability and evolutionary patterns in South American CPV populations. We collected samples from puppies suspected of CPV infection in the neighboring Argentina and Uruguay. Antigenic variants were preliminarily characterized using PCR-RFLP and partial vp2 sequencing. Samples collected in Argentina during 2008-2018 were mainly of the 2c variant. In the Uruguayan strains (2012-2019), the 2a variant wholly replaced the 2c from 2014. Full-length coding genome and vp2 sequences were compared with global strains. The 2c and 2a strains fell by phylogenetic analysis into two phylogroups (Europe I and Asia I). The 2c strains from Argentina and Uruguay clustered in the Europe I group, with strains from America, Europe, Asia, and Oceania. Europe I is widely distributed in South America in the dog population and is also being detected in the wildlife population. The 2a strains from Uruguay formed the distinct Asia I group with strains from Asia, Africa, America, and Oceania. This Asia I group is increasing its distribution in South America and worldwide. Our research reveals high genetic variability in adjacent synchronic samples and different evolutionary patterns in South American CPV. We also highlight the importance of ancestral migrations and local diversification in the evolution of global CPV strains.